A comprehensive review on walnut protein: Extraction, modification, functional properties and its potential applications - Mingxin Zhang; Shengbao Cai; Ou Wang; Lei Zhao; Liang Zhao (Journal of Agriculture and Food Research, 2024)
Plant proteins, as sustainable resources with various health benefits, have gradually been widely researched as substitutes for animal proteins. Walnut protein, as a plant-based protein source, is rich in essential amino acids and has a reasonable proportion of eight essential amino acids, making it a potential high-quality protein that has attracted widespread attention. The potential application of walnut protein as a sustainable protein source is summerized in this review. Firstly, the amino acid composition, protein classification, and functional properties of walnut protein were discussed. Secondly, the main limitations of walnut protein utilization were discussed, such as anti-nutritional factors, poor functional properties, and allergenicity were discussed. Finally, commonly used modification methods, including physical methods, chemical methods, biological methods, and backbone hybridization technology to improve the functional characteristics of walnut protein, as well as its potential application for use in the food industry were summarized. This review provides new ideas for its development and utilization.